A Digital Halal Lifestyle Strategy in the Development of Muslimah Fashion MSMEs: Case Study of Amelda Fashion in Silirejo Village - Sofa Nazilatul Khusna; Hendri Hermawan Adinugraha; Ade Gunawan (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2025)
The Muslim fashion industry has grown rapidly along with increasing public awareness of the halal lifestyle. This research examines the digital halal lifestyle strategy of Amelda Fashion, a Muslimah fashion MSME in Silirejo Village. Using a qualitative approach, data were collected through observations of live shopping sessions on TikTok and Shopee, as well as in-depth interviews with the business owner. The findings show that Amelda integrates live shopping, value-based pricing, trend-based design innovation, and e-commerce data utilization. This strategy supports efficiency, strengthens halal identity, and is relevant to the dynamic capabilities theory in value-based MSME development.